Educational approach for public health ethics in nursing: Focusing on COVID-19 - Byun, Hye Min (Nursing ethics, 2024)
BackgroundWith the increasing ethical challenges and dilemmas faced by nurses due to various disasters such as COVID-19 worldwide, there is a need for a new public health ethics education curriculum to strengthen competencies for ethical responses in the nursing field.ObjectivesThis study was aimed to identify the impact of a teaching method utilizing news articles and panel discussion material in the public health ethics education program on nursing students’ thinking regarding ethical issues.DesignThis was an exploratory study to identify the thinking styles inherent in ethical reflection by analyzing the reflection contents written by nursing students using text mining techniques.Participants73 among the students taking a nursing ethics course at a university in Seoul, South Korea, voluntarily participated in this study after providing informed consent.MethodsThe public health ethics program was conducted with sessions held once a week for a total of 7 weeks, and reflections written by nursing students were collected as text files during session 5 to 7. In this study, data preprocessing process, keyword analysis, and LDA topic modeling were sequentially conducted utilizing the R program according to the data analysis procedure of text mining techniques.Ethical considerationsThis study was conducted under ethics approval from the institution where participants were recruited.Findings and discussionThe results of this study show that the teaching method utilizing news articles enhanced rational ethical deliberation from the cognitive aspect, whereas the teaching method utilizing panel discussion material strengthened the response to emotions on a more internal level.ConclusionsThe teaching method utilizing news articles and panel discussion materials in public health ethics education is expected to be mutually complementary and effective, so further studies are recommended.